Transformation of Learning Media Through TikTok: A Qualitative Study of the Influence of Viral Media "UBUR-UBUR" - Vedianty, Adinda Syalsabilla Aidha; Lestari , Andika Setyo Budi; Rayungsari, Maya (Journal of Teaching and Learning Mathematics, 2024)
Technological developments have brought significant changes in learning methods. This research aims to explore the transformation of mathematics learning media through TikTok with a focus on the influence of viral content with the theme "Ubur-uber". The research methodology used is qualitative with a phenomenological approach. Data was collected through direct observation and analysis of relevant TikTok content. From the results of observations, 50 Ubur-uber-themed videos were selected based on the criteria of popularity and user interaction. Data were analyzed using thematic analysis techniques to identify main patterns and themes. The focus of the research lies in the use of Ubur-Ubur content in mathematics learning media and its impact on the teaching and learning process. The findings show that TikTok is an effective platform in the world of education, where viral Ubur-Ubur content has succeeded in making mathematics learning more interesting and efficient for students and educators. Concrete examples include increased student participation in class discussions and a better understanding of the material. The results of this research show that learning media innovation through platforms such as TikTok can make a positive contribution to the world of education. However, it was discovered that the Ubur-Ubur content on TikTok has never been researched and published in a national or international journal to test its effectiveness in terms of the validity of the media used, etc. This shows that this media is only a learning innovation, especially mathematics. By leveraging the viral nature of Ubur-Ubur content, educators can create more dynamic and interactive learning experiences. This research provides insight into the potential of TikTok as an effective educational tool and opens up opportunities for further exploration of the use of social media for educational purposes, especially in mathematics subjects.